Efficiency improvement in wood beam line process using Lean Manufacturing tools in peruvian sawmill industry - Lopez Acosta, Jose Manuel (2024)
The research aimed to improve the operational efficiency in the cutting process of a wood beam line in a Peruvian sawmill using Lean Manufacturing tools. The study found a technical gap of 11.81% with an economic impact of 4.94%. Three root causes were identified: breakdowns in the tableting machine, high setup times, and errors in the cutting process. To address these issues, the study proposed the use of engineering tools such as SMED and standardization of the work method. The implementation of these tools was expected to increase operational efficiency, reduce downtime, and improve product quality. The study's findings contribute to the literature on Lean Manufacturing and its application in the Peruvian manufacturing industry, highlighting the potential for efficiency improvements in the wood processing sector.